Money and finance : readings in theory, policy and institutions - Carson, Deane (New York : Wiley, 1966)
The book discusses elementary facts about monetary demand and supply, along with materials that supplement the chapters.
Includes bibliographical footnotes.
osc 07/05/2018
Loans
Keywords: Money; Banks and banking